2014
DOI: 10.7717/peerj.636
|View full text |Cite
|
Sign up to set email alerts
|

Elaborate cellulosome architecture ofAcetivibrio cellulolyticusrevealed by selective screening of cohesin–dockerin interactions

Abstract: Cellulosic waste represents a significant and underutilized carbon source for the biofuel industry. Owing to the recalcitrance of crystalline cellulose to enzymatic degradation, it is necessary to design economical methods of liberating the fermentable sugars required for bioethanol production. One route towards unlocking the potential of cellulosic waste lies in a highly complex class of molecular machines, the cellulosomes. Secreted mainly by anaerobic bacteria, cellulosomes are structurally diverse, cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…The residues that participate in dockerin recognition are mostly invariant in the three cohesins (data not shown), suggesting that ScaC can accommodate three ScaB proteins via the recognition of the C-terminal dockerin module. In addition, a second A. cellulolyticus protein termed ScaJ, accession number WP_010243813, contains a single N-terminal cohesin module that shares extensive similarity with the ScaC cohesins, primarily at the residues important for protein recognition (13,19). ScaJ also contains a C-terminal SLH domain, which suggests that, like ScaC, it constitutes an anchoring scaffoldin with the ability to recognize a single ScaB molecule.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…The residues that participate in dockerin recognition are mostly invariant in the three cohesins (data not shown), suggesting that ScaC can accommodate three ScaB proteins via the recognition of the C-terminal dockerin module. In addition, a second A. cellulolyticus protein termed ScaJ, accession number WP_010243813, contains a single N-terminal cohesin module that shares extensive similarity with the ScaC cohesins, primarily at the residues important for protein recognition (13,19). ScaJ also contains a C-terminal SLH domain, which suggests that, like ScaC, it constitutes an anchoring scaffoldin with the ability to recognize a single ScaB molecule.…”
Section: Tablementioning
confidence: 99%
“…Comparison of A. cellulolyticus with C. cellulolyticum and C. thermocellum Type I Coh-Doc Complexes-It was previously observed that the A. cellulolyticus type I DocScaB specifically recognizes type I cohesins of ScaC and will not bind type I cohesins of ScaA or type I cohesins from C. thermocellum or C. cellulolyticum (19). This lack of cross-specificity between CohDoc pairs of different species may assist accurate and efficient assembly of a coherent set of enzymes into each cellulosome.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Coh-contacting residues at positions 11 and 12 (numbering established considering the first Gly of each calcium binding loop as residue 1), which are thought to be the major specificity determinants of all type I Docs (3), are different in the ScaB and enzyme type I Docs. Differences at these key residues may explain why there is a lack of cross-specificity between the type I Doc interactions that modulate the binding of ScaB onto ScaC or the cellulosomal enzymes onto ScaA (10,21). It is possible, however, that other elements of the two type I Doc species confer their observed distinct specificities.…”
mentioning
confidence: 99%